Problems of Student Competency in the Department of History Education and Students' Historical Awareness of the Utilization of Historical Sites - Nurasiah, Nurasiah; Azis, Abdul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
The purpose of this article is to explore students' historical awareness is the understanding of individual aspects, ideas, thoughts, desires, and memories related to historical events or historical sites found in various regions. Students' historical awareness also includes a dimension of knowledge that leads to individual competencies. This study utilised qualitative research, employing historical methods. The population consisted of 350 students, while the sample size for this study was 23 students. The data collection techniques used were primary data, including interviews, document analysis, and artefacts, while the secondary sources were books and documents. The data analysis techniques used were heuristics, verification, interpretation, and historiography. The results of the study show that the problem of the competence of students of the History Education and historical awareness study program lies in the lack of knowledge about local historical sites as a whole. In other words, the problem of lack of interest in reading also affects knowledge of local historical sites, and the low value of students' historical awareness was also seen in previous studies. The contribution of this research lies in sharpening the perspective in looking at the historical awareness of students from the fundamental perspective of the interests of History Education students.